Effect of temperature and colonization of Legionella pneumophila and Vermamoeba vermiformis on bacterial community composition of copper drinking water biofilms. Issue 4 (18th January 2017) - Buse, Helen Y.; Ji, Pan; Gomez‐Alvarez, Vicente; Pruden, Amy; Edwards, Marc A.; Ashbolt, Nicholas J.
Summary: It is unclear how the water‐based pathogen, Legionella pneumophila (Lp), and associated free‐living amoeba (FLA) hosts change or are changed by the microbial composition of drinking water (DW) biofilm communities. Thus, this study characterized the bacterial community structure over a 7‐month period within mature (> 600‐day‐old) copper DW biofilms in reactors simulating premise plumbing and assessed the impact of temperature and introduction of Lp and its FLA host, Vermamoeba vermiformis (Vv), co‐cultures (LpVv). Sequence and quantitative PCR (qPCR) analyses indicated a correlation between LpVv introduction and increases in Legionella spp. levels at room temperature (RT), while at 37°C, Lp became the dominant Legionella spp. qPCR analysis suggested Vv presence may not be directly associated with Lp biofilm growth at RT and 37°C, but may contribute to or be associated with non‐Lp legionellae persistence at RT. Two‐way PERMANOVA and PCoA revealed that temperature was a major driver of microbiome diversity. Biofilm community composition also changed over the seven‐month period and could be associated with significant shifts in dissolved oxygen, alkalinity and various metals in the influent DW. Hence, temperature, biofilm age, DW quality and transient intrusions/amplification of pathogens and FLA hosts may significantly impact biofilm microbiomes and modulate pathogen levels over extended periods.